KOMPOSISI KERTAS KARTON BERSERAT DARI LIMBAH BATANG DAN TANDAN KOSONG KELAPA SAWIT - Hasmawaty (Politeknik Negeri Sriwijaya, 2016)
Oil palm is very economic and high value, for every each part of the oil palm can bring the benefit to the owner. The waste that came from its stem and its old shell can be used as seeders. Its stem and its cluster can be considered as an alternative material standard in developing paper industry. So that it is necessary to analyzes the composition of fibrous carton paper in stem and in an empty cluster from oil palm, in order to get the paper which is fulfill the quality standard of paper. From the result, it can be interpretation that the percentage of average composition came from an empty cluster; cellulose (36,9%), lignin (16,5%), and hemi-cellulose (27,2%). In contrary the average percentage that came from stem: cellulose (36,56%), lignin (16,4%), and hemi-cellulose (26%). From the analyzes, that paper which is going to be taken is fibrous carton paper.